Pensando el ser de la naturaleza: la φύσις en el pensamiento griego, ocultamiento y movimiento - Cuenca, Maribel (2019)
This article aims to address the notion of nature and its problematic character, from the discussion and reflection that triggers the question of being for the philosopher Martin Heidegger. I highlight, throughout the text, the original link between the question of being and Greek thought about phýsis. For this, it will be essential to pay attention to Heraclitus in his approach to phýsis and its concealment; Aristotle’s reflections on the subject also represent an important contribution, based on his concern about the relationship between phýsis and movement. Finally, from the history of being we will try to underline the beginning of the decline of phýsis and the emergence of nature.